The Role Of Teaching Aids In Supporting Differentiated Pedagogy Among Arabic Language Teachers - Muhamad Iman Wedad Dawod; Mohammad Taufiq Abdul Ghani (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
21st-century education demands that educators cater to the diversity of student potential, particularly following the abolition of the class streaming system in 2019, which created mixed-ability classes. However, the unreadiness of Arabic language teachers, who often remain bound by traditional methods, has been found to hinder the student learning process. Therefore, this study aims to explore the role and integration of Teaching Aids in supporting the implementation of Differentiated Pedagogy among Arabic language teachers. This qualitative study employs a case study design using semi-structured interviews with experienced Arabic language teachers at Jawahir Al-Ulum Religious High School, Johor. The data analysis outlined four main themes: selection strategies for Teaching Aids based on student inclination and cognitive levels; effective characteristics of Teaching Aids encompassing real materials and multimedia; suitability measurement mechanisms through teacher reflection; and implementation challenges involving resource, time, and training constraints. Overall, the study concludes that Teaching Aids function as a critical strategic instrument, not merely a support tool, in bridging student cognitive gaps. The implications suggest that teacher training programs should be empowered with innovations in Teaching Aid development to ensure a more effective and inclusive implementation of Differentiated Pedagogy in Arabic language education.